Lumbung Mathematics (LUMMATH): Pembelajaran Geometri Kontekstual Berbasis Rumah Adat Sasak Guna Menciptakan Pembelajaran Interaktif - Hafizin, M. Khoirul; Choirunnisa; Iskandar; Dwi Novitasari (Rengganis Jurnal Pengabdian Masyarakat, 2025)
The Lumbung Mathematics (LUMMATH) program was developed to address the low learning interest and numeracy skills of students at the Darurrahman NW Aik Ampat Islamic Boarding School, where general subjects, especially mathematics, receive less attention. To make geometry learning more concrete and meaningful, this program presents a miniature Sasak traditional house (Bale Lumbung) and a contextual exploration-based worksheet (LKPD). The implementation program includes media guidance for teachers, classroom learning assistance, and geometry explorations compiled by students. The implementation results showed a significant improvement, with the average student learning outcome score increasing from 54.65 in the pre-test to 80.23 in the post-test and 81.4% of students achieving the Minimum Competency (KKM), while based on the results of the learning interest questionnaire, the learning interest increased by 83.25%. Students were more active in discussing, measuring, and analyzing miniature components, while teachers showed improved facilitation skills after participating in the guidance session. These findings indicate that the integration of local cultural objects through the LUMMATH media is effective in strengthening conceptual understanding, increasing learning motivation, and fostering students' appreciation of Sasak culture